Collective Negotiations and the Work Environment Systematic Literature Review - Huamán, Anthony Carmen; Sánchez, Lorena Beatriz Tume; Talledo, Luis Rubén Castillo (Journal of Ecohumanism, 2024)
This systematic review, based on an exhaustive search of databases such as scopus, SciELO, Redalyc, Dialnet, Erih Plus, Latindex, the University César Vallejo library, explored the relationship between collective bargaining and work climate over the past five years. Empirical studies that quantitatively or qualitatively analyzed the impact of collective bargaining on work climate-related variables, such as satisfaction, commitment, and perceptions of fairness, were included. Theoretical studies, narrative reviews and those not published in the last five years were excluded. The results indicate that collective bargaining has a positive impact on the perception of work climate, increasing employees’ satisfaction and their perception of fairness. In addition, it was identified that collective bargaining influences specific aspects of the work climate, such as communication, trust, and engagement. The findings suggest that a positive work climate, fostered by collective bargaining, is associated with better organizational performance. However, further research is required to fully understand the underlying mechanisms and the generalization of these results to different contexts.